2020
DOI: 10.1038/s41467-019-14143-9
|View full text |Cite
|
Sign up to set email alerts
|

REEP5 depletion causes sarco-endoplasmic reticulum vacuolization and cardiac functional defects

Abstract: The sarco-endoplasmic reticulum (SR/ER) plays an important role in the development and progression of many heart diseases. However, many aspects of its structural organization remain largely unknown, particularly in cells with a highly differentiated SR/ER network. Here, we report a cardiac enriched, SR/ER membrane protein, REEP5 that is centrally involved in regulating SR/ER organization and cellular stress responses in cardiac myocytes. In vitro REEP5 depletion in mouse cardiac myocytes results in SR/ER memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 77 publications
(86 reference statements)
4
11
0
Order By: Relevance
“…In parallel experiments, we also demonstrated knockdown of gene expression in these cells, further emphasising the utility of the cellular isolation methodology. Specifically, as the SR adaptor protein Reep5 is known to be essential in maintaining cardiac function 23 , AAV9-mediated Reep5 shRNA knockdown ( Fig. 4d) was performed and cells were analyzed at d3 or d4.…”
Section: Resultsmentioning
confidence: 99%
“…In parallel experiments, we also demonstrated knockdown of gene expression in these cells, further emphasising the utility of the cellular isolation methodology. Specifically, as the SR adaptor protein Reep5 is known to be essential in maintaining cardiac function 23 , AAV9-mediated Reep5 shRNA knockdown ( Fig. 4d) was performed and cells were analyzed at d3 or d4.…”
Section: Resultsmentioning
confidence: 99%
“…(receptor paraprotein 5) leads to defects in cardiac function and vacuolation of the endoplasmic reticulum [39]. A missense mutation (p. G274R) in the ASPA (aspartate acylase) gene caused Canavan disease in a Pakistani family [40].…”
Section: Discussionmentioning
confidence: 99%
“…1a ). Our earlier studies focused on two of these proteins, TMEM65 and REEP5, in detailed biochemical analyses, identifying their specific roles in regulating cardiac conduction and cardiac muscle sarcoplasmic reticulum organization and function, respectively 10 , 12 . Here, we performed a detailed analysis of all 550 identified cardiac membrane proteins and showed that GO term-associated classifications demonstrated 50% of the identified protein clusters had a predicted transmembrane domain and 60% of them contained the GO term “membrane” (Fig.…”
Section: Resultsmentioning
confidence: 99%